Zinc Sulfide Decorated on Nitrogen‐Doped Carbon Derived from Metal‐Organic Framework Composites for Highly Reversible Lithium‐Ion Battery Anode. Issue 22 (18th November 2019) - Ding, Hui; Huang, Hsin‐Chih; Zhang, Xin‐Ke; Xie, Lei; Fan, Jia‐Qi; Jiang, Tao; Shi, Dean; Ma, Ning; Tsai, Fang‐Chang
Abstract: On account of its low cost, non‐toxicity and high theoretical capacity, ZnS has been considered as one of the most potential anode materials for the following generation lithium‐ion batteries. However, the shortcomings that ZnS shows, such as low conductivity and large volume changes, make its wide application difficult. Herein, we combined ZnS with metal‐organic framework material (ZIF‐8) to form a carbon layer on the surface of nitrogen‐doped zinc sulfide, and obtained a new material ZnS@NC with a specific surface area of 191 m 2  g −1 . The results show that the reversible specific capacity of the composite is 853 mAh g −1 when the current is 500 mAg −1, which is caused by the increase of specific capacity with nitrogen doping and the effective adjustment of the volume of the carbon layer coated on the periphery of the ZnS particles during charging and discharging process. Promisingly, the performance of ZnS@NC composite is far superior to that of the bare ZnS. Abstract : Simple but effective : ZIF‐8 with an average grain size of 35 nm was uniformly distributed on the surface of ZnS doped with nitrogen. Finally, the composite material was carbonized in Ar atmosphere. Through nitrogen doping and carbon encapsulation, the composite has excellent long‐term cyclic stability, excellent rate capability, and high reversibility. At 0.5 C current density and 450 cycles, 853 mAh g −1 can still be maintained. The composite material has simple synthesis method and good lithium storage capacity. It is an ideal choice for advanced anode materials.